주택통계의 품질향상을 위한 개선방안 - 성태영(Tae-Young Seong); 이만형(Man-Hyung Lee) (한국비교정부학보, 2010)
This study focuses on measuring the quality of housing census originally carried out in 2005. In order to suggest a series of alternative methods to improve the overall quality of housing statistics, it covers five sectors designated by the Statistics Korea: quality management bases, Focus Group Interviewing and users’ satisfaction level, treatment procedures, accuracy of collected data, and error level of publicized data. The followings are major findings. First of all, it should strengthen strategies of treatment procedures. Basically, it has to keep the consistency and comprehensiveness of housing statistics. In addition, it has to develop new housing indicators which would reflect the dynamic transformation of society. Secondly, it pays attention to providing appropriate statistical milieu and statistical methods. Here, the top priority should be given to the training of interviewees who would herald in collecting housing dada. Thirdly, it should keep in mind that the statistical data should be user-friendly. Also, it should upgrade its status quo, facilitating international comparison between housing statistics. KCI Citation Count: 6